GLOBAL CITIZENSHIP EDUCATION (GCE): ROLE AND IMPLEMENTATION IN SUSTAINABLE DEVELOPMENT - Lisdri Sustiwi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The purpose of this article is to analyze the role and implementation of Global Citizenship Education (GCE) in sustainable development amidst globalization that is full of challenges. This study uses a qualitative approach with a literature study method. This study examines the thoughts of Sara Franch and other figures in various perspectives on global citizenship and their relevance in reconfiguring citizenship education. The results of the study indicate that the practice of Global Citizenship Education (GCE) in its implementation in various Educational Institutions tends to focus on the aspects of qualifications and socialization. This focus leads to the unification of discourse oriented towards the development of global competence, which not only includes mastery of 21st century skills, but also prioritizes the formation of character and values ​​of responsible, ethical, and participatory global citizenship. Global Citizenship Education (GCE) is identified as a means to prepare the younger generation to face an alternative, inclusive, and sustainable world. Seeing this, efforts to achieve sustainable development can only be achieved by promoting global social justice. This study emphasizes the importance of a subjectification approach, which is based on social justice and critical deconstruction of the dominant discourse.